Creative information seeking and interface design - Foo, Schubert (2009)
Inspired by Weisberg’s argument that everyone is creative, this paper highlights a model of information seeking capturing users’ creative traits by synthesizing established models in information seeking and creativity. Using Google, a pilot study was conducted to understand subjects’ creative information seeking process. Claims Analysis and Interaction Framework were used to elicit design features that might have supported subjects’ creative, “serendipitous” information seeking. This paper presents novel, initial work towards eliciting conceptual design features for users’ creative, “serendipitous” information seeking behaviors. It concludes with a discussion on creativity and interface design for information retrieval systems.